Revisiting Literature in Times of Pandemics: The Relevance of Cultural Studies for Literary Analysis - Nanang Endrayanto (Universitas Brawijaya, 2021)
In trying to integrate science into the policy-making process, authorities and the public commonly overlook the essential role of literature in dealing with the COVID-19 pandemic. A close examination of the topic shows that it is more complex than the authorities’ commitment to science. “We follow the science” is a way of communicating rather than implementing. Since other articulations are excluded in the articulation of “we follow science,” cultural and critical studies become crucial. Arguably, literature communicates science better than the strategy adopted by the ruling elites.